Power Sharing in a Divided Nation : Mediated Communalism and New Politics in Six Decades of Malaysia's Elections - Saravanamuttu, Johan (Book collections on Project MUSE., 2016)
This book argues that Malaysia's electoral politics have historically been premised on a hybridized model of communalism and consociationalism. Beyond this it posits a newer idea of power sharing based on the dynamic and transformative practice of mediated communalism through six decades (1952-2016) of electoral politics. The strategy of mediating communalism is critically explored throughout the book, serving to test its saliency as a distinct approach to power sharing in a social formation which is ethnically, religiously and regionally divided, yet has remained remarkably and tenuously integrated throughout Malaysia's electoral history. The book delves into this question by narrating and theorizing the complexity of communal politics leading to the emergence of new politics which have attempted to put Malaysia on the track of further democratization. It is further implied that new politics has to work in tandem with mediated communalism to transcend the most deleterious effects of an ethnically divided society.